(untitled) (Research, Society and Development, 2023)
Dengue has solidified itself as an endemic disease in tropical countries, where climatic conditions favor the development of the vector mosquito, Aedes aegypti. In this context, it is currently the most relevant arbovirus in Brazil, being a compulsorily notifiable disease due to its status as a public health problem. Objective: To establish an epidemiological profile of dengue in the municipality of Jacareí – SP, correlating details of the behavioral and sociodemographic profile obtained in the survey with specific epidemiological data of dengue recorded in the municipality. Methods: A survey was conducted through an online questionnaire using the Google Forms platform for residents of Jacareí and its neighboring cities. The access link was shared on social media. Results: Considering the inclusion and exclusion criteria, the survey comprised 145 participants, with a higher participation of women (100), young adults aged 21 to 29 years (68), and those with completed high school education (60). Among participants infected with dengue, higher infection rates were observed in women (54.2%), the elderly (26.1%), and residents of the eastern zone (29.2%). A high infection rate was also observed in elderly individuals with low educational attainment. Regarding dengue prevention, directly related to covering any container that accumulates stagnant water, it was observed that this is the most adopted prophylaxis among participants (87.7%). Conclusion: Dengue is endemic in the Jacareí region, presenting higher incidences in more vulnerable groups such as women and elderly individuals with low educational attainment, emphasizing that access to information is key to knowledge and safety.